Equivalence of sequential Henstock and topological Henstock integrals for interval valued functions - Victor Iluebe; Adesanmi Mogbademu (Journal of Mahani Mathematical Research, 2023)
Suppose $X$ is a locally compact Hausdorff space and $\Omega \in \bigtriangleup$. If $ F $ is an interval valued function defined in $ \Omega $ with $F:\bar \Omega\rightarrow I_{\mathbb{R}}$. Suppose $F$ is Topological Henstock integrable, is $ F $ Sequential Henstock integrable? Therefore, the purpose of this paper is to provide a positive response to this query.